The queer manifesto: Imagining new possibilities and futures for marketing and consumer research. (June 2022) - Pirani, Daniela; Daskalopoulou, Athanasia
In this manifesto, we explore how queer theory can contribute to expanding what we consider legitimate knowledge within marketing research. Previous scholars in marketing and management have highlighted the potential of queer theory, remarking how little it is used within the discipline. Reviewing marketing scholarship that uses queer theory shows how it is mostly applied in relation to the Lesbian, Gay, Bisex, Trans and Queer (LGBTQ+) consumers and contexts, reproducing the same dualism it challenges. To overcome this, we provide a brief outline of the theory, leading to five research avenues that are relevant to marketing: gender and sexuality; phenomenology; desire; failure and methodology. Each of these avenues considers how queer lenses have been and could be applied within our discipline. We stress that the epistemological value of queer theory is in valuing the margins, rejecting dualism and questioning the hierarchies of power within capitalism. In the utopian logic of the manifesto, we do not intend to provide guidelines, but horizons of possibility for marketing and consumer theorisation.